Anti-NMDAR encephalitis misdiagnosed as Hashimoto's encephalopathy - Mirabelli-Badenier, M; Biancheri, R; Morana, G; Fornarino, S; Siri, L; Celle, M; Veneselli, E; Vincent, A; Gaggero, R; Mancardi, M (2014)
Anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis is a well-defined autoimmune disorder. Hashimoto's encephalopathy (HE) is a still controversial entity, lacking definite diagnostic criteria. We described a 14-year-old-girl presenting with a clinical picture consistent with the diagnosis of anti-NMDAR encephalitis, confirmed by NMDAR antibody testing. Four years earlier, she had presented a similar episode of acute encephalopathy diagnosed as HE. Anti-NMDAR encephalitis and HE share similar clinical features so that the differential diagnosis can be difficult if specific antibodies are not tested. The correct diagnosis of anti-NMDAR encephalitis is crucial to plan the appropriate management and follow-up, namely in term of oncological screening, since it can be paraneoplastic in origin. We suggest to re-evaluate the clinical history of all subjects with previous HE diagnosis in order to evaluate the possible diagnosis of anti-NMDAR encephalitis and plan the appropriate management of these patients. © 2013 European Paediatric Neurology Society. Published by Elsevier Ltd. All rights reserved.